Generation of an induced pluripotent stem cell line (UMi043-A) from an African American patient with Alzheimer’s disease carrying an ABCA7 deletion (p.Arg578Alafs) - Holly N. Cukier; Shaina A. Simon; Eugene Tang; Charles G. Golightly; Mayra Juliana Laverde-Paz; Larry Deon Adams; Takiyah D. Starks; Jeffery M. Vance; Michael L. Cuccaro; Jonathan L. Haines; Goldie S. Byrd; Margaret A. Pericak-Vance; et al. (Stem Cell Research, 2024)
The ATP-binding cassette, subfamily A (ABC1), member 7 (ABCA7) gene is associated with Alzheimer’s disease (AD) risk in populations of African, Asian, and European ancestry1-5. Numerous ABCA7 mutations contributing to risk have been identified, including a 44 base pair deletion (rs142076058) specific to individuals of African ancestry and predicted to cause a frameshift mutation (p.Arg578Alafs) (Cukier et al., 2016). The UMi043-A human induced pluripotent stem cell line was derived from an African American individual with AD who is heterozygous for this deletion and is a resource to further investigate ABCA7 and how this African-specific deletion may influence disease pathology.